Maui-VIA: A User-Friendly Software for Visual Identification, Alignment, Correction, and Quantification of Gas Chromatography–Mass Spectrometry Data - Kuich, P. Henning J. L.; Hoffmann, Nils; Kempa, Stefan (Frontiers in Bioengineering and Biotechnology, 2015)
A current bottleneck in GC MS metabolomics is the processing of raw machine data into a final datamatrix that contains the quantities of identified metabolites in each sample. While there are many bioinformatics tools available to aid in the initial steps of the process, their use requires both significant technical expertise and a subsequent manual validation of identifications and alignments if high data quality is desired. The manual validation is tedious and time consuming, becoming prohibitively so as sample numbers increase. We have therefore developed Maui VIA, a solution based on a visual interface that allows experts and non experts to simultaneously and quickly process, inspect, and correct large numbers of GC MS samples. It allows for the visual inspection of identifications and alignments, facilitating a unique and, due to its visualization and keyboard shortcuts, very fast interaction with the data. Therefore, Maui Via fills an important niche by 1) providing functionality that optimizes the component of data processing that is currently most labor intensive to save time, and 2) lowering the threshold of expertise required to process GC MS data. Maui VIA projects are initiated with baseline-corrected raw data, peaklists, and a database of metabolite spectra and retention indices used for identification. It provides functionality for retention index calculation, a targeted library search, the visual annotation, alignment, and correction interface, metabolite quantification, as well as the export of the final datamatrix. The high quality of data produced by Maui VIA is illustrated by its comparison to data attained manually by an expert using vendor software on a previously published dataset concerning the response of Chlamydomonas reinhardtii to salt stress. In conclusion, Maui VIA provides the opportunity for fast, confident, and high quality data processing validation of large numbers of GC MS samples by non experts.